2013
DOI: 10.1002/pamm.201310274
|View full text |Cite
|
Sign up to set email alerts
|

Infinite Penalization for Optimal Control Problems: An infinite‐dimensional optimization method for constrained optimization problems

Abstract: We present results on a method for infinite dimensional constrained optimization problems. In particular, we are interested in state constrained optimal control problems and discuss an algorithm based on penalization and smoothing. The algorithm contains update rules for the penalty and the smoothing parameter that depend on the constraint violation. Theoretical as well as numerical results are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another approach to deal with this problem numerically is to approximate the non‐smooth penalty term by family of smooth functions. For problems with inequality constraints, this approach has been studied in and .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach to deal with this problem numerically is to approximate the non‐smooth penalty term by family of smooth functions. For problems with inequality constraints, this approach has been studied in and .…”
Section: Resultsmentioning
confidence: 99%
“…In [24], it is shown that this problem is equivalent to the problem The form (35) of the Neumann optimal boundary control problems allows to show an interesting result on the structure of the optimal controls: For initial states with velocity zero, that is, y 1 D 0, there exists an optimal control that is odd with respect to the midpoint of the time interval. More precisely, we have the following:…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation